An operational conceptualization to establish island contribution to the economy (Comercio y Negocio, 2018)
Attention is not paid to ghost islands (Priam, 2004, p. 60).  Islands can be part of a continental State, an insular State, or pertaining to none. Climate Change makes those geographical entities more visible than before, defined as "a land surrounded by water in all parts". In our opinion it is urgent to recognize those pieces on international, regional and local maps (Priam, 2016). This article results from a review of the global literature regarding the definition of islands that demonstrates a gap regarding conceptualization in that field. We published in 2016 a book that presents a conceptualization for islands under "simple insularity" and "double insularity" (Priam J., 2016, BiblioServices, 234 p.) that was first presented during the 2006 CIEMADES Conference in Puerto Rico. From an economic point of view, islands participate to the economy of a State and global economy. Our operational conceptualization allows such considerations. We illustrate our analysis through a case study of an island part of the archipelago of Guadeloupe. The economic vision has been the one to "eliminate the backwardness caused by their isolation or remoteness". Our approach is at the opposite that allows to give visibility to the enhancement of the economy due to political and ecological solidarities. A recent group of Brazilian islands and action taken for Venezuelan islands show such new trends we have to work on. The ongoing United Nations work to identify islands worldwide shows need to better integrate them in the future.